OXIDATION OF BENZYLIC SECONDARY ALCOHOL WITH PYRIDINIUM CHLOROCHROMATE-ALUMINA (PCC-Al2O3) - Hanoch J. Sohilait (Universitas Gadjah Mada, 2008)
In these studies, Pyridinium chlorochromate-Alumina was used for oxidation of secondary alcohols (safryl alcohol and methyleugenyl alcohol) to ketone. The oxidation of safryl alcohol with PCC-Al2O3 followed by purification by potassium bisulfite yields safryl ketone (62,92%). The oxidation of methyleugenyl alcohol with PCC-Al2O3, followed by purification by potassium bisulfite yields methyleugenyl ketone (68,04%). The elucidation of these products was analyzed by FTIR, 1H-NMR and MS.